Affection of the constitutional right to the personal integrity of the women and the members of the family group in the family violence process, Mixed Court of Alto de la Alianza, Tacna-year 2016. - Quiñones Talledo, Charles Harrinson (2019)
An investigation was carried out regarding the affectation of the constitutional right of the personal integrity of the women and the members of the family group in the process of family violence in the joint high court of the Tacna alliance in 2016, in consideration of Law No. 30364. 218 family violence cases were analyzed and 127 surveys were applied to the victims who were affected in their personal integrity. The investigation aims to demonstrate the existence of the violation of the constitutional right to personal integrity and regarding the operation of protective measures to safeguard the personal integrity of the victims and their effectiveness, as for approximately half of the victims, they did not avoid recidivism or new aggressions on the part of the aggressors. However, it is necessary to implement a technical proposal that contains new legal and administrative procedures that allow the determination of a better procedure both in the monitoring and control of its application for the protection of victims. Said proposal contemplates the granting of a greater participation of the Mixed Court or Family Module of the CSJT. Likewise, the elaborated proposal considers the creation of the position of Protective Lawyer, who would be attached to the Family Module as part of the multidisciplinary team and would be responsible for verifying compliance with the protection measures and the safeguarding of personal integrity as a fundamental right of the victims. The reform of the application of the Protection Measures contemplates new legal and administrative mechanisms that should be included in a law amending the regulation of violence against women and members of the family group currently in force, given that there is a great deal of impact on the personal integrity of the victims.